2015
DOI: 10.1002/pon.4016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a combined physical and psychosocial intervention program for childhood cancer patients on quality of life and psychosocial functioning: results of the QLIM randomized clinical trial

Abstract: A combined physical and psychosocial training for children with cancer did not have effects on HrQoL or psychosocial functioning, with exception of modest positive effects on parent-reported pain and procedural anxiety Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 32 publications
1
72
1
10
Order By: Relevance
“…Finally, this was a post hoc analysis of the QLIM study in which no distinction was made between the intervention and the control group. Even though no significant effect of the combined physical exercise and psychosocial training program on physical fitness was found, there may have been some beneficial effects of participating in the QLIM study on an individual level that may have influenced our results.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Finally, this was a post hoc analysis of the QLIM study in which no distinction was made between the intervention and the control group. Even though no significant effect of the combined physical exercise and psychosocial training program on physical fitness was found, there may have been some beneficial effects of participating in the QLIM study on an individual level that may have influenced our results.…”
Section: Discussionmentioning
confidence: 88%
“…There were no significant beneficial effects of the QLIM intervention on physical fitness, physical and psychosocial function at 4 and 12 months, except for a larger improvement in lower body muscle strength at 12 months in the intervention group. [26][27][28] Therefore, patients were evaluated together for the purpose of the present study, irrespective of the QLIM study group they were originally assigned to.…”
Section: Discussionmentioning
confidence: 99%
“…The randomization process was adequately specified in five studies and in three studies it remained unclear . Four studies included patients during the maintenance phase: two studies indicated the timing as “after diagnosis” and in two studies the treatment phase was not specified .…”
Section: Selected Studies Analysismentioning
confidence: 99%
“…Given the documented impact of emotional health on quality of life, combining physical exercise interventions with psychosocial training during this time period would seem reasonable if the goal of intervention was to also improve quality of life. However a small randomized trial evaluating combined physical exercise and psychosocial training indicates that intervention does not result in appreciable differences in either fitness or health related quality of life if administered during or in the first year after cancer therapy [39]. It may be that interventions delivered this early that also require significant exertion and cognitive attention are too difficult for children to participate in while they are acutely ill.…”
Section: Potential Interventions For Fitness and Quality Of Life In Cmentioning
confidence: 99%